Issues and challenges of auditing in Islamic financial institutions - Mathew Kevin Bosi; Melissa Della Joy (Valley International, 2017)
The Islamic Finance Institutions (IFIs) has gained international recognition as a viable and vibrant component of the global financial system. As a matter of fact, Islamic Finance has seen an increased adoption across the globe, and is growing faster than any other industry at a rate of 15 to 20 percent a year. This study aims to expand the literature relating to IFIs and to provide a coeval outlook on the issues and challenges of Shari’ah audit in IFIs specifically in Malaysia. Hence, the earlier part of this study explains the current auditing standards for IFIs and the roles of Shari’ah auditors, followed by a close look up on the issues and challenges facing the audit of IFIs such as the standards and regulatory requirements of Shari’ah audits, independence of Shari’ah auditors and qualification as well as the accountability of the Shari’ah auditors. This study concludes that there is a need of regulatory framework specifically designed for Shari’ah audits along with the need of independent and accountable Shari’ah auditors to conduct the audit of IFIs.